Wood-inhabiting aphyllophoroid basidiomycetes: diversity, ecology and conservation - Küffer, Nicolas (My University, 2007)
Wood-inhabiting aphyllophoroid basidiomycetes are a species rich and ecologically significant group in nemoral and boreal forests. They are divided in three major morphological groups: corticioid, poroid and thelephoroid basidiomycetes. The species richness and species distribution depend on several features on different scales: the diversity of the provided substrate, i.e. dead wood, is of vital importance on a smaller scale. On a larger scale the direct (i.e. amount of dead wood, natural likeness) and indirect (i.e. forest fragmentation, distance between fungal populations) impact of forestry highly influences the fungal species richness, additionally to site specific (i.e. altitude, exposition, slope) and regional (i.e. biogeographical region) characteristics. For the quality of dead wood as substrate for wood-inhabiting fungi, three features are most essential: size of dead woody debris, degree of decomposition and host tree species. These characteristics and their combinations create a wide variety of niches subsequently colonised by a great number of fungal species. Especially the often neglected smallest fraction of dead woody debris, i.e. thin branches and twigs, are rich in species. Woody shrub species and thermophilic tree species host a particularly rich fungal species set, as many aphyllophoroid species are host-selective. Additionally, the amount of dead woody substrate is equally important, especially in managed forests. Evidently, the amount and the composition of dead woody substrate are strongly influenced by forest management practices, where most dead wood is cleared and a siteadapted tree cover is often ignored. On a larger scale, the management history of a forest is very important: the time since the last forestry intervention seems a good indicator to predict fungal species richness, at least when dealing with strongly managed Central European forests. Furthermore, if intensive forest management results in habitat fragmentation, the fungal species richness is heavily affected. Fragmentation may not only occur spatially, but also temporally: a break in the availability of the dead woody substrate disrupts the continuity of the fungal life cycle and so causes the local disappearance of populations. When considering the high degree of substrate specialisation of most fungal species, this temporal break in the substrate availability is a major threat for fungal populations in managed nemoral forests. Considering these findings, the remnant patches of natural forest in Central Europe should harbour a considerably higher amount of wood-inhabiting aphyllophoroid basidiomycetes. However, the results of this study are equivocal. Despite the presence of a higher quantity of dead wood and of more diverse dead wood as substrate, which clearly favours the woodinhabiting basidiomycetes, the analyses could not reveal statistically relevant differences.
Thèse de doctorat : Université de Neuchâtel, 2007 ; Th.1989
Keywords: Basidiomycètes; diversité; écologie forestière; bois mort; débris du bois; décomposition; gestion des forêts; Basidiomycetes; diversity; forest ecology; dead wood; woody debris; decomposition; forest management